Impaired neurotransmission in ether lipid-deficient nerve terminals - Brodde, Alexander; Teigler, André; Brügger, Britta; Lehmann, Wolf-Dieter; Wieland, Felix T.; Just, Wilhelm W. (Human molecular genetics, 2012)
Isolated defects of ether lipid (EL) biosynthesis in humans cause rhizomelic chondrodysplasia punctata type 2 and type 3, serious peroxisomal disorders. Using a